Check your English vocabulary for leisure, travel and tourism / Rawdon Wyatt - Wyatt, Rawdon
This workbook provides exercises to help teach and build English vocabulary relevant to the hotels, tourism and catering industries. It has been written for both students studying towards professional exams and for those who want to improve their specialist communication skills.